THE JOER: VOICES OF PARENTS, TEACHERS AND MANAGERS ABOUT STUDENTS (Fiep Bulletin - online, 2024)
Introduction:The School Games are a national event that promotes an enriching learning and competition environment for students. Objective:It was to understand how student participation in the Rondônia School Games is evaluated by different parts of the school community (parents, teachers and management). Methods:The methodology adopted was field research. The samples were: 10 parents, 4 teachers and a manager, from futsal finalist schools. Results:The results emphasize social, physical and emotional improvements in children. Parents highlighted the importance of Games for expanding children's knowledge. Methods used for selections: interest and behavior. Positive aspects mentioned: school visibility, family proximity, travel and better performance. Challenges were listed in relation to the school routine (extra-class training and lack of extra pay). The manager emphasized the impact of the Games on the school (sense of victory and belonging). Government financial support was considered essential. Conclusion: It is concluded that there was a positive view from both parents, teachers and the manager regarding the participation of students in the School Games, however teachers faced difficulties regarding training.
Keywords: School games; School Community; Perception